Evaluation of Stereotactic Radiotherapy of the Resection Cavity After Surgery of Brain Metastases Compared to Postoperative Whole-Brain Radiotherapy (ESTRON)—A Single-Center Prospective Randomized Trial. Issue 3 (8th March 2018) - El Shafie, Rami A; Paul, Angela; Bernhardt, Denise; Hauswald, Henrik; Welzel, Thomas; Sprave, Tanja; Hommertgen, Adriane; Krisam, Johannes; Schmitt, Daniela; Klüter, Sebastian; Schubert, Kai; Klose, Christina; et al.
Abstract: BACKGROUND: Neurosurgical resection is recommended for symptomatic brain metastases, in oligometastatic patients or for histology acquisition. Without adjuvant radiotherapy, roughly two-thirds of the patients relapse at the resection site within 24 mo, while the risk of new metastases in the untreated brain is around 50%. Adjuvant whole-brain radiotherapy (WBRT) can reduce the risk of both scenarios of recurrence significantly, although the associated neurocognitive toxicity is substantial, while stereotactic radiotherapy (SRT) improves local control at comparably low toxicity. OBJECTIVE: To compare locoregional control and treatment-associated toxicity for postoperative SRT and WBRT after the resection of 1 brain metastasis in a single-center prospective randomized study. METHODS: Fifty patients will be randomized to receive either hypofractionated SRT of the resection cavity and single- or multisession SRT of all unresected brain metastases (up to 10 lesions) or WBRT. Patients will be followed-up regularly and the primary endpoint of neurological progression-free survival will be assessed by magnetic resonance imaging (MRI). Quality of life and neurocognition will be assessed in 3-mo intervals using standardized tests and EORTC questionnaires. EXPECTED OUTCOMES: We expect to show that postoperative SRT of the resection cavity and further unresected brain metastases is a valid means of improving locoregional control over observation at less neurocognitive toxicity than caused by WBRT. DISCUSSION: The present study is the first to compare locoregional control as well as neurocognitive toxicity for postoperative SRT and WBRT in patients with up to 10 metastases, while utilizing a highly sensitive and standardized MRI protocol for treatment planning and follow-up.